Meaningful and Interesting Learning Process: Accomodating Comprehensible Input for Teaching English to Young Learners in the 4.0 Industrial Age - Dewi Cahyaningrum; Sandi Naftali; Cica Nur Hayati (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2020)
In general, the purpose of teaching young learners is to develop students’ physical aspects, intelligence, social-emotions, personality, language and communicative competence. Addressing the challenge of the 4.0 Industrial age, teachers of young learners need to know well the characteristics of millennial generation and must be adaptive to accommodate the growth of technology to support learning process. Teachers need to support young learners’ witn learning process held in a meaningful and interesting way stimulating the ability of young learners to think critically and creatively. Besides, learning process accommodating rich content of media and opportunities for interaction/ discussion with teachers and peers prepare both, high achievers and low achieversfor lifelong learning. In simple words, meaningful and interesting learning in this study covers some principles as follows; (1) accommodating comprehensible input; (2) accommodating active - collaborative learning, and (3) adopting and adapting online learning sites for young learners. Through this conditioning learning atmosphere, students' affective filters becomes lower and their learning process becomes more effective.